A review of methods for strengthening of masonry arches with composite materials. (15th September 2018) - Zampieri, Paolo; Simoncello, Nicolò; Tetougueni, Cyrille Denis; Pellegrino, Carlo
Highlights: The effectiveness of the strengthening techniques is strongly related to the reinforcing materials. The position of the reinforcement plays an important role in the failure mechanism of the arch. The kinematic ductility of arch structure are improved when reinforcement are located at the arch extrados. Imperfections should be considered in numerical analysis in order to get same results of experiment tests. Abstract: Strengthening of existing structures have been widely investigated around the world with the aim to preserve historic heritage and monument. Traditional techniques are being abandoned in favour to composite materials considered as innovative. Several authors have recently investigated techniques using carbon fibre, glass fibre, steel rod or other fibre materials as strengthening material of masonry arches the last two decades. This paper reviews the experimental campaigns conducted by several international researchers with the aim to bring new insights on the effectiveness of strengthening techniques using composite materials. A database of over 100 experimental tests have been analysed considering different arch parameters and interesting results on the role played by the position and the type of the reinforcement have be found.